2013
DOI: 10.26529/cepsj.226
|View full text |Cite
|
Sign up to set email alerts
|

Enjoying Cultural Differences Assists Teachers in Learning about Diversity and Equality. An Evaluation of Antidiscrimination and Diversity Training

Abstract: The present study is based on a quasi-experimental research design and presents the results of an evaluation of Antidiscrimination and Diversity Training that took place at the Faculty of Education in Ljubljana, rooted in the anti-bias approach to educating diversity and equality issues (Murray & Urban, 2012). The experimental group included 52 in-service early childhood teachers attending the training, which consisted of a total of 120 hours. There was also a control group comprising 130 teachers. The ADT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…These studies demonstrated how such PD efforts can improve the use of home language in the classroom (i.e., Daniel & Pray, 2017;Spies et al, 2017) or lead to higher teacher responsiveness and less disciplinary referrals of black children (i.e., ). Yet, in many interventions reflection was used to target teachers' belief systems rather than actual practice or behavior (e.g., Jones & Brown, 2015;Lazar & Offenberg, 2011;Psalti, 2007;Turnšek, 2013). These studies used reflection to help teachers investigate who they are and to make them aware of how their own cultural background influences their practices.…”
Section: Rq3: the Role Of Reflection And Enactmentmentioning
confidence: 99%
“…These studies demonstrated how such PD efforts can improve the use of home language in the classroom (i.e., Daniel & Pray, 2017;Spies et al, 2017) or lead to higher teacher responsiveness and less disciplinary referrals of black children (i.e., ). Yet, in many interventions reflection was used to target teachers' belief systems rather than actual practice or behavior (e.g., Jones & Brown, 2015;Lazar & Offenberg, 2011;Psalti, 2007;Turnšek, 2013). These studies used reflection to help teachers investigate who they are and to make them aware of how their own cultural background influences their practices.…”
Section: Rq3: the Role Of Reflection And Enactmentmentioning
confidence: 99%